EFFECT OF INVENTORY VALUATION METHODS ON PROFITS. - King, Robert W. (The Accounting Review, 1947)
Abstract Any company which sells merchandise to which it has a title ordinarily has inventories on hand at the beginning and end of each accounting period. The inventory on hand at the end of the period appears on the balance sheet as an asset, and is also taken into consideration in the income statement in determining cost of goods sold. It is immediately apparent, therefore, that the method of pricing the inventory at the beginning and end of each accounting period will have an important effect on both the balance sheet and the income statement. Stated in another way, if the method of pricing inventories allows an overstatement of the final inventory, then the asset value appearing on the balance sheet will be overstated. Similarly, the cost of goods sold on the income statement will be improperly stated, the amount depending upon the pricing errors in both the opening and closing inventories. It is a matter of extreme importance, therefore, that every company in which inventories play an important part should, in preparing its financial statements, follow a consistent and well-devised method of inventory pricing. Failure to do so will result in inaccurate and inconsistent financial statements, and will also result in inaccurate costing of goods sold during any accounting period.